Citric acid mediated green synthesis of copper nanoparticles using cinnamon bark extract and its multifaceted applications. (10th April 2021) - Sarwar, Nasir; Humayoun, Usama Bin; Kumar, Mohit; Zaidi, Syed Farrukh Alam; Yoo, Jung Hyeon; Ali, Nawaz; Jeong, Dong In; Lee, Jung Heon; Yoon, Dae Ho
Abstract: Copper nanoparticles are of great interest to researchers due to their diverse applications ranging from electronics to strong disinfectant. However, their synthesis involves the utilization of toxic reducing agents. Owing to the increased environmental awareness green synthesis including biosynthesis of nanoparticles is widely investigated. However, the poor reduction power of natural extract is a big challenge that limits the large-scale adaptation of the biosynthesis. Considering the importance of green processing, we propose a facile, biogenic one-step synthesis and capping of copper nanoparticles using cinnamon bark extract as a potential non-toxic reducing cum stabilizing agent. Citric acid, mediation was used in the synthesis process to promote reducing action of cinnamon along with modifying the surface morphology of as-synthesized nanoparticles. The as synthesized citric acid mediated nanoparticles presented a uniform spherical morphology with consistent surface texture. The catalytic performance of as-synthesized copper nanoparticles against mutagenic methylene blue (MB) and methyl orange (MO) dyes was evaluated using sodium hypophosphite (SHP) with above 80% of color degradation not reported previously. Further, the broad-spectrum disinfection property of as-synthesized nanoparticles, as an antimicrobial finish, can open a new horizon of development in the field of medical textile, personal protective equipment, and related applications. Graphical abstract: Image 1 Highlights: Green synthesis of copper nanoparticles was carried out using cinnamon bark extract as an effective bio reducer. Citric acid mediation was done as a sustainable booster to promote cinnamon reduction. Catalytic degradation of mutagenic dyes was explored using sodium hypophosphite for the first time. Broad spectrum disinfectant properties against gram-positive and gram-negative bacteria.